In Search of Enigmatic Individuals: A Psychoanalytic Discussion on Willa Cather’s My Mortal Enemy - Afreen, Sumaiya (Green University Review of Social Sciences, 2022)
Enigma is a ubiquitous essence in characters of 19th century American literature which commonly refers to the sarcastic or mysterious meaning of human life. America subsequently received great literary works encompassing contemporary provincial life including the haul of capitalism, versatile artistry along with unfolding of bemused human mindset. American stories, prior to the era of modernism were mostly magnified and critiqued with socio-economic perceptions rather than being scrutinized with concentrated psychoanalytic studies. Willa Cather's My Mortal Enemy illustrates bewildered minds of people. Central characters of the story are inflicted with the pursuit of worldly attainments. Extreme divergence amid the characters` desire and reality has left the whole story into paranoia. Myra Henshawe, the protagonist of the novella is a neurotic crippled patient who has deserted her soul`s aesthetic beauty under the grasp of terrestrial obsession and disturbing psychosomatic pattern. Jacques Lacan's three stages of psychic development will be maneuvered in this paper to evince the uncanny of shared life in Cather's story. The novella has a fictional as well as real time setting where people are found to sprint for materialistic self-indulgence. Cather has crafted some rare and intriguing discovery of seeking one`s mortal enemy in such an enigmatic plot which will complement the psychogenic discussion of the paper. This paper emits a critical study on how the characters turn as indecipherable in My Mortal Enemy by spot lighting on Freudian construction of ego, sublimation, desires and Lacanian psychoanalytic models. Green University Review of Social Sciences Dec 2021; 7(1-2): 75-88